The Effect Of Improving Competence, Career And Work Discipline On Performance With Occupational Safety And Health As Variable Intervening In The Network And Construction At Pt. Pln (Persero) Up3 Sibolga - Fachru Rozie Siregar; Elfitra Desy Surya (Utan Kayu Publishing, 2025)
This study aims to examine the effect of competence, career, and work discipline on employee performance at PT. PLN (Persero) UP3 Sibolga, with Occupational Safety and Health (OSH) as an intervening variable. The research employs a quantitative approach with an explanatory research design. Data was collected through questionnaires distributed to 53 respondents working in the network and construction department. The data analysis technique used was path analysis to test the direct and indirect relationships between the variables. The results indicate that competence, career, and work discipline have a positive and significant effect on employee performance, both directly and indirectly through OSH as an intervening variable. Competence and work discipline were found to enhance performance by improving OSH conditions, while career development influenced performance through increased awareness of OSH. This study provides important contributions in clarifying the role of OSH as a mediator in the relationship between factors affecting performance. The findings also offer recommendations for PT. PLN (Persero) to strengthen the development of competence, career management, and work discipline, as well as to ensure more effective OSH policies to improve employee performance.